Abnormal Heart Rate Recovery and Duke Treadmill Score as Predictor of Cardiovascular Mortality - YB Utomo (Faculty of Medicine, Public Health and Nursing Universitas Gadjah Mada, 2017)
Background: The Duke Treadmill Score (DTS) has been well validated and widely used for .....